Isolation and physical characterization of the MUC7 (MG2) mucin from saliva: evidence for self-association. - Mehrotra, R (1998)
Saliva contains two major families of mucins (MG1 and MG2); the polypeptide of the smaller of these glycoproteins (MG2) has been assigned as the product of the MUC7 gene. In this study we have devised a rapid two-step procedure that recovers this glycoprotein essentially free of other components and in sufficient quantity to enable physical and self-interaction studies. Raw saliva was solubilized in 4 M guanidinium chloride and thereafter subjected to Sepharose CL-4B chromatography. The MG2-rich fraction was recovered free from the larger MG1 glycoproteins and also smaller proteins/glycoproteins (molecular mass less than 100 kDa). MG2 glycoproteins were finally purified by anion-exchange chromatography on Mono Q. The purity of the preparation was assessed by SDS/PAGE after radiolabelling of the molecules with [14C]acetic anhydride. Peptide mapping, N-terminal sequencing and amino acid analysis verified the polypeptide of the mucins as the MUC7 gene product. The isolated molecules were examined by electron microscopy and appeared as short flexible worm-like structures 30-120 nm in length. The distribution was heterogeneous, containing a major component with number-average and weight-average lengths of 52 and 55 nm respectively and a minor component with number-average and weight-average lengths of 94 and 98 nm respectively. We propose that the two differently sized populations represent monomeric and dimeric species of the mucins. Gel chromatography performed in 0.2 M NaCl indicated the presence of monomers, dimers and tetramers; an average molecular mass for the preparation was 192 kDa. However, in 4 M guanidinium chloride the molecular mass was 158 kDa and a similar molecular mass (155 kDa) was determined for the mucin preparation after reduction. These results suggest that the mucins might self-associate via a protein-mediated interaction. On the basis of the results a model is proposed for the self-association of the MUC7 mucin, which might be important for its biological function.